As a biopatch, fibrin and bone marrow-derived cells modulate macrophage polarization and cardiomyobasts proliferation. (25th November 2020) - Borrego, I; Frobert, A; Cook, S; Giraud, M.N
Abstract: Introduction: Repair of the cardiac structure and function is the holy grail for curative treatment of myocardial infarction (MI). Clinical trials for cardiac cell-based therapies have revealed numerous challenges and led to a shift in the initial paradigms. The current concept is that cell/matrix-based therapy modifies the local immune response, releases factors involved in tissue repair, mitigates the progression of ventricular remodelling, and rescues the cardiac function. Macrophages are critical players in cardiac remodelling post-MI with a complex role yet not fully elucidated in cell-based therapy. Purpose: We, first, investigated in an MI animal model, the myocardial macrophage content following an epicardial application of a biopatch composed of bone marrow-derived cells (BMDCs) and fibrin-based matrix. Second, we analyzed in vitro the cell interactions between the biopath, macrophages and cardiomyoblasts. Methods: Two weeks post-infarct, performed on female rats, a Cell and Matrix BioPatch (CMBP) composed of fibrin and BMDCs was administered. Heart function and infarct were evaluated by high-resolution echocardiography and histology. Macrophages present 4 weeks post-MI were quantified by immunostaining for CD86 and CD206. In vitro, macrophages (undifferentiated (M0), triggered by IL4 (M2) or LPS/IFN-d (M1)), or cardiomyoblasts (H9C2) were cultured with conditioned media from CMBP. Their proliferation and plasticity were assessed by EDU incorporation and real-time cell analyzer and RT-PCR. Results: Our data showed a significant improvement in ejection fraction after treatment and a reduced infarct expansion index (IEI MI/untreated= 0.08±0.05 vs. IEI MI/CMBP_treated =0.22±0.09, p=0.002). The ratio of CD86+/CD206+ cells was also significantly reduced in treated compared to untreated groups (ratioMI/untreated=0.96±0.82 vs ratioMI/fibrin_treated=0.51±0.12 and ratioMI/CMBP_treated=0.17±0.13, p<0.05) suggesting an alteration of the macrophage polarization. In vitro assays with CMBP-conditioned medium revealed a significant increase in the proliferation of M0 and M2. Also, M0 were polarized towards an M2 profile. A switch of M1 toward M2 was revealed by Gene expression profiles with a reduction of pro-inflammatory markers (CD86, MCP-1, IL-1beta, CD80, RANTES and iNOS) and an increase in the anti-inflammatory ones (Arginase 1, CD163, CD106). The secretion profile of the macrophages was also modified with a lower secretion of IL-6 and TNF-alpha and increased IL-10. Interestingly, when cardiomyoblasts are cultured with the medium conditioned of the macrophages triggered by CMBP, their proliferation was significantly increased by 16%±1 with M0 or M2 and 18%±1 with M1. Conclusion: Our data point to a new paracrine communication from a biopatch that triggered macrophages and indirectly cardiac cells. Cell cross-talks promoted an anti-inflammatory response that promoted cardiac cells proliferation. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): University of Fribourg